Exploring Belief Values in Batu Umang Folklore: A Cultural Analysis of Durin Tani Village, Sibolangit District, Deli Serdang Regency - Situmorang, Sarma; Sinaga, Dewi Sartika; Simbolon, Soter (Insan Akademika Publications, 2023)
This research delves into the belief values embedded in the Batu Umang folklore of Durin Tani Village, located in the Sibolangit District of Deli Serdang Regency, North Sumatra, Indonesia. Through a comprehensive and multidisciplinary approach, the study uncovers the intricate web of cultural, social, and historical factors that have shaped these belief values, shedding light on their origins, evolution, and contemporary significance. The cultural context of the Batak people in Durin Tani Village plays a central role in the development of these belief values, with a deep reverence for nature and a harmonious relationship with the environment at its core. Social dynamics, including close-knit community bonds and shared values of unity and collective responsibility, have reinforced these belief values, fostering a sense of community cohesion. The historical backdrop of Dutch colonialism, trade, and migration has left an indelible mark on the folklore, imbuing it with stories of resilience and adaptability in the face of historical challenges. This research contributes significantly to the fields of folklore and cultural anthropology, highlighting the preservation of cultural heritage, community cohesion, and the adaptability of cultural traditions. It also underscores the universal nature of storytelling and belief systems, providing insights into the interconnectedness of culture, society, and history in shaping the belief values of a unique community. Ultimately, this study celebrates the enduring spirit of Durin Tani Village and its timeless cultural heritage, offering a deeper understanding of how local narratives can provide insights into the universal human experience.